2021
DOI: 10.5194/mr-2-265-2021
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical cell for in operando <sup>13</sup>C nuclear magnetic resonance investigations of carbon dioxide/carbonate processes in aqueous solution

Abstract: Abstract. In operando nuclear magnetic resonance (NMR) spectroscopy is one method for the online investigation of electrochemical systems and reactions. It allows for real-time observations of the formation of products and intermediates, and it grants insights into the interactions of substrates and catalysts. An in operando NMR setup for the investigation of the electrolytic reduction of CO2 at silver electrodes has been developed. The electrolysis cell consists of a three-electrode setup using a working elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…This constitutes a shift of the HCO -3 /CO 2 equilibrium towards HCO -3 , caused by an increasing local pH. The FWHM decreases due to faster exchange between carbonate species, which has been observed before by in operando NMR studies with silver working electrodes 25 . The fitting parameters exhibit fluctuations that can be attributed to gas bubble formation on the electrode during the electrochemical experiments.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…This constitutes a shift of the HCO -3 /CO 2 equilibrium towards HCO -3 , caused by an increasing local pH. The FWHM decreases due to faster exchange between carbonate species, which has been observed before by in operando NMR studies with silver working electrodes 25 . The fitting parameters exhibit fluctuations that can be attributed to gas bubble formation on the electrode during the electrochemical experiments.…”
Section: Resultssupporting
confidence: 59%
“…The cell holder presented in our previous publication 25 was adjusted such that the cell can be inserted from the top of the magnet with a narrow-bore sample lift installed. During CA, 13 C spectra were continuously recorded using 30°-pulses with 1 H decoupling (WALTZ-16 sequence with 128 repetitions every 2 s), resulting in acquisition of one spectrum every 6 min.…”
Section: Nmr Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This constitutes a shift of the / equilibrium towards , caused by an increasing local pH. The FWHM decreases due to faster exchange between carbonate species, which has been observed before by in operando NMR studies with silver working electrodes 25 . The fitting parameters exhibit fluctuations that can be attributed to gas bubble formation on the electrode during the electrochemical experiments.…”
Section: Resultssupporting
confidence: 58%
“…In this study, the measurement of pH is demonstrated in an electrochemical cell and during electrolysis by in operando nuclear magnetic resonance (NMR), which has proven capable of investigating the (aq)/ / equilibrium in such an environment 25 . The method takes advantage of the high spectral resolution and sensitivity afforded by this cell design even in the presence of electrically conductive material 26 .…”
Section: Introductionmentioning
confidence: 99%